MIX-MEDIA NARRATIVES WORKSHOP: MULTIDISCIPLINARY TEAMS’ PRODUCTION - Sonia Liliana da Silva Vieira; Luis Manuel Frias (Gestão & Tecnologia de Projetos, 2017)
The development of creation and content production teams, regarding design and digital publishing areas, their processes and transdisciplinary knowledge, are making deep changes in media production structures, and in its own professional sustainability model. The Mix-media Narratives Workshop that took place at Universidade da Beira Interior (Portugal) intended to simulate the reality of production structures and the recent integrated digital writing paradigm, as well as to evaluate the several multi and transdisciplinary challenges that may be present in the creation of digital media contents. Design, journalism and film production students were not only confronted with real editorial development situations, but also with professional feedback, which was possible due to a partnership with the newspaper Expresso.pt. A fellow editor from this newspaper kept track of the sessions, with the help and presence of professors from many of the courses involved. Data gathered from observation notes, pictures and video during laboratorial work meetings, was compiled and crossed with research results, analyses and comments made by the participant professors and Expresso. pt editor’s observations. Our goal was to analyze in which way future workers will deal with the challenging task of collaborating with multidisciplinary teams and produce mix-media content with real publishing purpose.